Economic analysis of implementing Systemic Coronary Risk Estimation (SCORE2) scale and long-term consequences - E. O. Kurilovich; A. V. Nikitina; I. V. Sorokovikov (Фармакоэкономика, 2024)
Objective: to assess the demand for pharmacotherapy in risk groups on adverse cardiovascular (CV) events identified during prophylactic medical examination of the adult population according to the SCORE2 (Systemic Coronary Risk Estimation) scale, which is being introduced into clinical practice.Material and methods. To analyze the economic consequences of including diagnostic examinations to assess the risk by SCORE and SCORE2 scales, a Markov model was developed, which described the course of lipid metabolism disorders in adult patients aged 40 to 69 years without concomitant diseases identified during prophylactic medical examination. The model cycle was 2 months (the average waiting time for response to therapy); the modeling horizon was 3 years; the calculated values were estimated for the period 2024–2026. The economic analysis of long-term consequences involved calculating the cost of pharmacotherapy and the costs associated with CV events at outpatient and inpatient stages of medical care. The costs of drug therapy were determined based on dosage regimens presented in instructions for medical use in Russia, and clinical guidelines.Results. According to the modeling results, in the period 2024–2026, the administration of pharmacotherapy to reduce the risks of CV events will enable to achieve 23,224 potentially saved lives through exclusively government funding or 23,605 through mixed sources of funding (government and citizens’ own funds). The cost of the analyzed pharmacotherapy upon the introduction of the SCORE2 scale will be from 50.18 billion rubles (with government funding) to 318.14 billion rubles. Concurrently, pharmacocorrection will provide a reduction in the costs of inpatient treatment and outpatient medical services to 4.1 billion rubles due to the achieving of intended low-density lipoprotein level, and 1.6 billion rubles due to the achieving of intended triglyceride levels.Conclusion. Using new SCORE2 scale may lead to changes in the practice of prescribing lipid-lowering prophylaxis of CV diseases, as well as to a sharp increase in the number of patients who may require earlier prescription of pharmacotherapy to prevent CV events.